Pengaruh Pemahaman Pengantar Akuntansi, Locus Of Control Dan Computer Anxiety Terhadap Hasil Belajar Myob (Mind Your Own Business) Accounting - Dewi Setiyaningsih Setiyaningsih; Angga Kurniawan Kurniawan; Elmira Febri Darmayanti Darmayanti (LPPM Universitas Pelita Bangsa, 2023)
The purpose of this study was to analyze the effect of Introductory Understanding of Accounting, Locus of Control, and Computer Anxiety on Learning Outcomes of MYOB (Mind Your Own Business) Accounting in students of the Bachelor of Accounting Study Program at Muhammadiyah Metro University. This type of research uses quantitative research with a population of 268 respondents. The sampling technique in this study used a purposive sampling technique so that 110 respondents were obtained. The results of this study indicated that the Understanding of Introductory Accounting had positive and significant effects on MYOB Learning Outcomes, Locus of Control had positive and significant effects on MYOB Learning Outcomes, and Computer Anxiety showed positive and significant effects on MYOB Learning Outcomes. In the simultaneous test, it was found that the understanding of introductory accounting, Locus of Control and Computer Anxiety jointly yielded positive effect on MYOB Learning Outcomes.